2019
DOI: 10.1088/1361-6668/aafc38
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic simulations of actual superconducting maglev systems considering thermal and rotational effects

Abstract: Recently, the application of high-Tc superconductors with longitudinal geometry to linear bearings and transportation devices has reached a higher stage of development. For these maglev systems, static stability has already been established; but dynamic stability is still under investigation, since these systems have multiple degrees of freedom and their dynamics are coupled with intricate superconducting phenomena. In this paper, in terms of Newton’s second law, the thermal diffusion equation, and Maxwell’s e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…This is because the flux inside the HTS bulk under higher vibration frequency is more intense. Other studies in the literature [15,16] have concluded that the levitation force is a little higher when not considering the thermal effect than when accounting for the thermal effect, because the attenuation caused by thermal loss is not considered. From this point of view, under the experimental vibration condition, the force attenuation without the thermal effect is a little smaller than the case considering the thermal effect, in which J c retains some mathematic relationships with temperature T during the calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the flux inside the HTS bulk under higher vibration frequency is more intense. Other studies in the literature [15,16] have concluded that the levitation force is a little higher when not considering the thermal effect than when accounting for the thermal effect, because the attenuation caused by thermal loss is not considered. From this point of view, under the experimental vibration condition, the force attenuation without the thermal effect is a little smaller than the case considering the thermal effect, in which J c retains some mathematic relationships with temperature T during the calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Using this linear formula, Tixador et al [14] calculated the current distribution and AC losses of the YBCO slab. In recent years, Ye [15] and Huang [16] studied the dynamic thermal effect of the HTS Maglev system using YBaCuO bulks by the linear J c –T relation.…”
Section: Introductionmentioning
confidence: 99%
“…The maximal strain of our Nb3Sn superconducting coil with an applied current of 700 A is about 0.9% which causes a severe decrease in critical current. Although the sensitivities of thermomagnetic instabilities to various electromagnetic and thermal parameters have been studied in experiments and numerical simulations [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], the effects of strain, filamentary size, and the field ramp functional form on the flux jump are still unclear. These parameters play a crucial role in the flux jump, so it is essential to reveal their influences on the superconducting magnets during the operation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of high temperature superconducting (HTS) phenomenon, HTS materials have attracted extensive interest in superconducting maglev studies [1][2][3][4][5][6][7][8][9] due to their unique properties. The interaction between an HTS bulk and a magnet guideway can produce both vertical levitation force and lateral guidance force, which is the unique feature of HTS maglev [10].…”
Section: Introductionmentioning
confidence: 99%